Do Internal Capabilities Affect Competitive Advantage? The Case of a Regional Owned Company - Maharani, Anita; Kartasunjaya, Tammy Kathlia (Faculty of Economics and Business, Universitas Negeri Yogyakarta in collaboration with the Institute for, 2024)
AbstractThis research aims to get an overview of the factors affecting organizational competitive advantage and to obtain insights into the most influential factors concerning organizational competitive advantage. This research used the Integrated Talent Management Scale, Utrecht Work Engagement Scale-9, Employee Satisfaction Scale, Employee Performance Scale, and Competitive Advantage Scale. This research followed a quantitative approach. Then the data used in this research was primary data. The researchers gathered data without intervention. This research followed the variance-based structural equation modeling with partial least squares (SEM-PLS) and used SMART PLS as a tool. This research collected 108 types of data by distributing surveys and using the Likert scale. The sampling method in this research was done through non-random sampling and purposive sampling. The questionnaires were distributed to a Jakarta regional owned enterprise. This research found that employee engagement has no impact on employee satisfaction or employee performance in a regional owned company, and employee satisfaction has no impact on competitive advantage in a regional owned company. Keywords:organization, competitiveness, advantage, factors